Role of interleukin-6 in the development of atherosclerosis in rheumatoid arthritis - Elena Vasilyevna Udachkina; D S Novikova; T V Popkova; E L Nasonov (Современная ревматология, 2013)
Rheumatoid arthritis (RA) is a chronic systemic autoimmune disease. Coronary vascular events caused by atherosclerosis are one of the leading causes of death in RA. The review gives the results of studies of the role of interleukin-6 (IL-6) in the development of autoimmune inflammation and cardiovascular diseases. The link between IL-6, inflammation, and blood lipid spectrum is considered. Attention is focused on the lipid-lowering and pleiotropic effects of statins. There is information of the effects of IL-6 receptor inhibitors (Tocilizumab – TCZ)) on blood lipid levels in RA. The implication of IL-6 in the pathogenesis of atherosclerosis in RA and the effects of TCZ on the development and progression of atherosclerosis need future investigations.